Aplikasi Absensi Pegawai Kantor BAPPEDA Kota Binjai Berbasis Website - Yunda Aidilia; Nia Zanah Nia; Sriani Sriani (Jurnal Ilmiah Sistem Informasi dan Teknik Informatika (JISTI), 2024)
Attendance is an important thing in government agencies. By having a good attendance system, it can help in controlling the work completion process in order to get optimal results and in accordance with the predetermined goals. This research aims to develop a Website-Based Attendance Application that can optimize employee attendance management at the Binjai City Bappeda office, and can also ensure that employee attendance complies with applicable rules and policies. This research uses the waterfall method to design and present a website-based employee attendance application for the Binjai City Bappeda office. The results of system testing are carried out using the black box testing method by observing the execution results through test data and verifying that the Software function really meets the criteria or is functioning. It can be concluded that the existence of this Website-Based Application system can help employees manage their absence time effectively.